Caffeic Acid Phenethyl Ester Ameliorates Calcification by Inhibiting Activation of the AKT/NF-κB/NLRP3 Inflammasome Pathway in Human Aortic Valve Interstitial Cells - Liu, Ming (Front Pharmacol, 2020)
Calcific aortic valve disease (CAVD) occurs via a pathophysiological process that includes inflammation-induced osteoblastic differentiation of aortic valvular interstitial cells (AVICs). Here, we investigated the role of the anti-inflammatory compound caffeic acid phenethyl ester (CAPE) in inhibiting CAVD. Human AVICs were isolated and cultured in osteogenic induction medium (OM) with or without 10 μM CAPE. Cell viability was assessed using CCK8 assays and calcified transformation of AVICs was evaluated by Alizarin Red staining and osteogenic gene/protein expression. RNA-sequencing was conducted to identify differentially expressed genes (DEGs) and enrichment in associated pathways, as potential molecular targets through which CAPE inhibits osteogenic induction. The regulatory effects of CAPE on activation of the AKT/NF-κB and NLRP3 inflammasome were evaluated by Western blot analysis and immunofluorescent staining. CAPE slowed the growth of AVICs cultured in OM but did not show significant cytotoxicity. In addition, CAPE markedly suppressed calcified nodule formation and decreased gene/protein expression of RUNX2 and ALP in AVICs. Gene expression profiles of OM-induced AVICs cultured with or without CAPE revealed 518 common DEGs, which were highly enriched in the NOD-like receptor, PI3K-AKT, and NF-κB signaling pathways. Furthermore, CAPE inhibited phosphorylation of AKT, ERK1/2, and NF-κB, and suppressed NLRP3 inflammasome activation in AVICs cultured in OM. Thus, CAPE is implicated as a potent natural product for the prevention of CAVD by inhibiting activation of the AKT/NF-κB pathway and NLRP3 inflammasome.